Formal Concept Analysis : 15th International Conference, ICFCA 2019: Frankfurt, Germany, June 25{u2013}28, 2019: proceedings /: 15th International Conference, ICFCA 2019: Frankfurt, Germany, June 25{u2013}28, 2019: proceedings. ([2019]) - Unknown
No abstract available